PENDAMPINGAN IBU MENYUSUI DALAM KEBERHASILAN PEMBERIAN ASI SEBAGAI UPAYA PEMENUHAN GIZI BAYI: ASSISTANCE OF BREASTFEEDING MOTHERS IN SUCCESSFUL BREAST MILK AS AN EFFORT TO FULFILL THE INFANT'S NUTRITION - KHOTIMAH, HUSNUL KHOTIMAH,; SUBAGIO, SRI UTAMI (LPPM Univ. Ibn Khaldun Bogor, 2021)
Breast milk is the best food for babies. The coverage of exclusive breastfeeding for infants aged 0-6 months is 80% nationally in Banten Province 65%. One of the efforts so that breastfeeding can run well if breastfeeding techniques and breast care are carried out properly. This community service activity uses the Community Development method (community empowerment). The activity is carried out in the period from May to June 2021. The location of the activity is at the Al Amin Medika Clinic, Serang City. The target of this community service activity is 15 nursing mothers. This activity is counseling, mentoring and providing modules on breastfeeding. The results of the questionnaire conducted on all participants found 3 (20%) mothers who did not give breast milk because the mother of the baby did not get information about the benefits of breastfeeding, but there was information about formula milk that many mothers encountered and working mothers. The pretest and posttest scores showed a change in the form of an increase in the number of participants who understood from 6 participants (40%) at the time of the pre-test then an increase in the number of participants who understood as many as 12 people (80%). There is an increase in post test results indicating that the assistance provided can provide knowledge and understanding to mothers about the importance of exclusive breastfeeding in forming good breastfeeding behavior, so that it will improve the health status of mothers and children.